Gender variances in Chinese and Korean requests: A continuum rather than polarity - Rue, Y.; Zhang, Grace (Common Ground Publishing, 2013)
This paper examines connections between gender and request strategies in Mandarin Chinese and Korean, a topic of relatively limited past research. Data was collected through role-plays, and data analysis was based on the coding system of the Cross-Cultural Speech Act Realization Project (Blum-Kulka, House and Kasper 1989). In terms of interactional styles (direct or indirect), both genders chose indirect head acts and downgrading supportive moves (external modifications) as the most preferred, to lessen the impositional force of a request. They differed in their degree of directness: men were somewhat more direct than women, and more adaptable in responding to power status (Chinese men) and social distance (Korean men). Women were more consistent in choosing an indirect approach regardless of variances in social factors. In using supportive moves, men were proactive, which helped them to mitigate the impact of a direct request; women were more defensive and passive. An important implication of this study is that gender variance is not categorically polarised, but there is a continuum between the two gender groups. With this understanding of a continuum rather than polarity, a better understanding of gender issues can be obtained.